New Curricular Approaches to Teaching About the Middle East and North Africa. Issue 1 (1st March 2015) - Hantzopoulos, Maria; Zakharia, Zeena; Shirazi, Roozbeh; Bajaj, Monisha; Ghaffar-Kucher, Ameena
Abstract : This paper explores the possibilities of engaging in cross-disciplinary research to generate social studies curricula that disrupt singular historical constructions about the Middle East and North Africa (MENA), specifically for US high school teachers and students. As part of a larger multi-sited study that investigated and analyzed the common categories used to describe and teach MENA in US World History textbooks, the team engaged in multidisciplinary scholarship on the region to (1) review and analyze the five most widely adopted high school World History textbooks in the US; (2) share analyses with researchers and experts in the fields of MENA studies, history, and religion; (3) synthesize and integrate innovative scholarship on the region for potential curricula; and (4) generate robust alternative curricula for Grades 9-12 teachers. The authors, consequently, consider how educational research spurs innovative and culturally relevant curricular interventions for high school teachers. We argue thorough analysis of existing textbooks, informed by deep understandings of contested versions of historical events, should undergird social studies curriculum development. We suggest multidisciplinary and transnational collaboration can inform curricula in order to respond critically to singular narrations of peoples, cultures, and histories of a region.